Assessment of corrosion control by pH neutralisation in the presence of glycol at low temperature - Pojtanabuntoeng, Kod; Kinsella, Brian; Ehsani, H.; McKechnie, J. (Elsevier, 2017)
© 2017 Elsevier Ltd. The effect of pH controlled by n-methyldiethanolamine (MDEA), partial pressure of CO 2 , and monoethylene glycol (MEG) on corrosion behaviour of carbon steel (X65) at 10 °C was investigated. Linear polarisation resistance and electrochemical impedance spectroscopy techniques were used. The optimum pH which yielded reasonable corrosion rate reduction was 6.5-7. While demanded impractical concentration of MDEA, increasing pH further to 8.5 marginally decreased corrosion rate as the reduction of bicarbonate ions became a dominant cathodic reaction. The double layer capacitance decreased in the presence of MEG indicating the adsorption of MEG at the steel surface and reduced corrosion rate.